A plea for the 'de-migranticization' of research on migration and integration1. Issue 13 (20th October 2016) - Dahinden, Janine
ABSTRACT: Migration and integration research has been institutionalized over the last few decades. However, an increasing number of voices has been calling for more reflexivity, criticizing the nation-state- and ethnicity-centred epistemology that often informs this discipline. Consistently with this line of reasoning, I argue that migration and integration research originates in a historically institutionalized nation-state migration apparatus and is thus entangled with a particular normalization discourse. Therefore, this field of study contributes to reproducing the categories of this particular migration apparatus. This entanglement poses some serious dilemmas for this research tradition, dilemmas that ask for further consideration and possible solutions. My main proposition is to 'de-migranticize' migration and integration research. I outline possible ways of doing so and discuss the consequences of such a strategy for the future of migration and integration studies.